Etos Kerja Pedagang Etnis Madura Perantau Di Pasar Natar Ditinjau Dari Etika Bisnis - Tri Wahyuni Widowati; Risma Margaretha Sinaga; Herpratiwi Herpratiwi (EKOMBIS REVIEW: Jurnal Ilmiah Ekonomi dan Bisnis, 2023)
The Indonesian population consists of various ethnic groups and ethnic groups spread throughout Indonesia. The many ethnicities and tribes in Indonesia certainly have a big influence on the diversity of economic, social and cultural activities. The purpose of this study was to find out in depth about the work ethic of Madurese ethnic traders in Pasar Natar in terms of business ethics. The approach used in this study is a descriptive qualitative approach. Respondents in this study were retail traders who specifically sell Madura satay from Bangkalan Regency. Primary data collection strategies, such as interviews, must contain consistent questions, namely consisting of the same questions posed to each source. Researchers must be able to connect and convey all the information obtained during the research. The results of the study show that the work ethic of the Madurese is to work hard and wander and have implemented business ethics well such as honesty, awareness of the social significance of business activities, not committing perjury, being friendly, not being able to discredit other people's business, measure, size, and correct scales. The work ethic of the Madurese, who is tenacious and hard working, is a genetic factor. The choice of place of business is one of the marketing strategies so that it has a good impact on the profits of Madura satay sellers, especially at the Natar Market.